SPECIFIC FEATURES OF THE DEVELOPMENT OF MORPHOLOGICAL CHANGES IN THE LUNGS IN EXPERIMENTAL ATHEROSCLEROSIS UNDER THE INFLUENCE OF VARIOUS RISK FACTORS - Karimov Akmal Raxmonovich (TADQIQOTLAR, 2025)
Annotation. Currently, among lung pathologies in the world, chronic obstructive pulmonary disease is the fourth leading cause of death worldwide, claiming 3.5 million lives in 2021, which is approximately 5% of all deaths worldwide. The study of changes in lung tissue in atherosclerosis is undoubtedly one of the urgent problems of modern morphology. Atherosclerosis is a systemic process, therefore, if damage is detected in one part of the body, the likelihood of atherosclerosis developing in other areas, including the lungs, is very high. In atherosclerosis, as a systemic disease, changes in the lungs can manifest as narrowing of the pulmonary arteries due to the formation of atherosclerotic plaques, which leads to impaired function and the development of symptoms such as shortness of breath.